hMAGEA2 as a potential diagnostic and therapeutic target for melanoma progression and metastasis: Effect of hMAGEA2 on melanoma - Yi, Junkoo; Kim, Chae Yeon; Kim, Hyeonjin; Kim, Eun Gyung; Kim, Do Yoon; Sung, Yonghun; Liu, Kang Dong; Choi, seong-kyoon; Ryoo, Zae Young; Park, Song; Kim, Myoung Ok (Cellular and Molecular Biology, 2024)
The incidence of melanoma, a highly aggressive skin cancer, continues to increase worldwide, particularly among populations with lighter skin tones. The diagnostic challenge of melanoma lies in the absence of a distinctive clinical presentation, as its characteristics vary based on anatomical location, growth type, and histopathology. The melanoma-associated antigen (MAGE) gene family is differentially expressed in various human cancers, including melanoma. In this study, we explored the association between human MAGEA2 (hMAGEA2) expression and melanoma. Using a human melanoma tissue array, we confirmed that hMAGEA2 expression was higher in melanoma and metastatic melanoma than in normal tissues. Additionally, we used SK-MEL-5 and SK-MEL-28 cell lines to investigate the cellular and molecular mechanisms underlying melanoma progression and invasiveness. In SK-MEL-5 and SK-MEL-28 cells, hMAGEA2 overexpression accelerated cell proliferation. Conversely, the knockdown of hMAEGA2 reduced cell proliferation, colony formation, and migration significantly and induced arrest at the G2/M phase of the cell cycle. With respect to the molecular mechanism, the knockdown of hMAGEA2 decreased the phosphorylation of Akt, JNK, and p38 MAPK. Additionally, hMAGEA2 knockdown reduced tumor formation significantly at the in vivo level. Collectively, the robust correlation between hMAGEA2 and melanoma metastasis supports the potential utility of hMAGEA2 as both a diagnostic marker and novel therapeutic target for patients with melanoma metastasis.